2012
DOI: 10.1128/aac.05274-11
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antiviral Activity of Topoisomerase I and II Inhibitors against Kaposi's Sarcoma-Associated Herpesvirus

Abstract: . To assess the importance of these topoisomerases in viral lytic replication, shRNA-mediated gene silencing was used. Depletion of Topo I and II severely inhibited viral lytic DNA replication as well as virion production, suggesting essential roles of these cellular proteins in viral DNA replication. The discovery of Topo I and II as enzymes indispensable for KSHV DNA replication raises a possibility that these cellular proteins could be new targets of therapeutic approaches to halt KSHV replication and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…KSHV and the other herpesviruses studied so far do not encode topoisomerases. Thus, it could be assumed that these viruses use cellular topoisomerases for the viral DNA replication (19,67). Indeed, the importance of TopoII␤ in KSHV lytic DNA replication was recently demonstrated (67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KSHV and the other herpesviruses studied so far do not encode topoisomerases. Thus, it could be assumed that these viruses use cellular topoisomerases for the viral DNA replication (19,67). Indeed, the importance of TopoII␤ in KSHV lytic DNA replication was recently demonstrated (67).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that gene silencing of TopoI and TopoII with specific short hairpin RNA (shRNA) or use of ellipticine, a specific inhibitor of TopoII, could abolish KSHV lytic DNA replication (19). Additionally, it has been shown that a wide variety of potential topoisomerase inhibitors effectively block KSHV lytic DNA replication and could be further screened as therapeutic drugs (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final DMSO concentration in the culture medium was maintained at 1%. For lytic replication, BCBL-1 cells were induced by tetradecanoylphorbol acetate (TPA) as previously reported (20). JSC-1 cells were induced by 3 mM sodium butyrate (22).…”
Section: Methodsmentioning
confidence: 99%
“…We also demonstrated that both Topo I and Topo II are indispensable for KSHV lytic replication and that specific inhibitors of Topo I and II can effectively inhibit KSHV lytic replication. One category of Topo II inhibitors, namely, catalytic Topo II inhibitor, was found to provide marked inhibition of KSHV replication with minimal cytotoxicity, as indicated by their high selectivity indices (e.g., 31.6 for novobiocin) (20). As such, Topo II can serve as an effective target for antivirals, and catalytic inhibitors of Topo II represent promising antiviral agents for the treatment of malignancies associated with KSHV infection.…”
mentioning
confidence: 99%